2003
DOI: 10.1136/oem.60.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Periportal fibrosis and other liver ultrasonography findings in vinyl chloride workers

Abstract: Aims: To investigate the presence of liver lesions and their relation with vinyl chloride monomer (VCM) exposure or other personal risk factors, in workers involved in the production of VCM and polyvinyl chloride (PVC). Methods: A liver ultrasonography examination was conducted in 757 workers, some of whom had long standing service in the production of VCM and PVC. The study involved: assessment of individual past and present VCM exposure of each worker; collection of past personal health history, lifestyle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group [76,207] PBB Electronics recycling industry; maintenance/repair technicians of PBB devices [209][210][211][212] Group 2A [207] Chloral 75-87-6 Insecticides and herbicide production; p...…”
Section: Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group [76,207] PBB Electronics recycling industry; maintenance/repair technicians of PBB devices [209][210][211][212] Group 2A [207] Chloral 75-87-6 Insecticides and herbicide production; p...…”
Section: Organic Solventsmentioning
confidence: 99%
“…induce specific gene mutations in the liver [105][106][107][108][109][110][111][112][113][114][115][116][117] . Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…The data presented in this paper have already been partly described in a former study (Maroni et al 2003).…”
Section: Methodsmentioning
confidence: 85%
“…Cumulative VCM exposures (ppm · years) were also computed and the workers grouped into five classes (0, 1-10, 11-100, 101-1000, > 1000 ppm · years). For more details on exposure assessment see Maroni et al 2003.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation